Principal space-related transformation processes demonstrated by maps of the atlas of eastern and southeastern Europe - Jordan, Peter (Journal for Geography, 2008)
The article highlights some principal transformation processes in the post-Communist transformation countries of Central and Southeast Europe. This comprises (1) environemtal change, (2) growing spatial disparities, (3) democratic transformation with a focus on administartive decentralisation and (4) the consequences of a rise in national and ethnic consciousness. As its main source this article is based on the Atlas of Eastern and Southeastern Europe, edited as a thematic map series since 1989 by the author of this article.
Keywords: transformation; Central Europe; Southeast Europe; environment; spatial disparities; administrative decentralisation; national consciousness